The Economics of Tobacco Taxation and Employment in Indonesia : Policy Implications - World Bank Group (World Bank, Washington, DC, 2018)
Indonesia has one of the highest rates of cigarette consumption in the world. Tobacco use heavily burdens population health, undermines the quest for universal health coverage, and inflicts heavy direct and indirect economic costs. Higher tobacco taxes to increase cigarette prices contribute to reducing tobacco consumption and hence tobacco-related disease and death, while increasing public resources for development. The Indonesian government has recently raised tobacco tax rates. This strategy has brought initial gains and should be aggressively ramped up. By raising tobacco taxes toward WHO-recommended levels (at least 70 percent of retail price) and streamlining its tobacco excise tax structure, Indonesia can rapidly cut smoking rates, save many lives, and boost government revenue. Such policies would contribute to realizing Indonesia's demographic dividend by keeping people healthy.